Aortic Arch Replacement without Deep Hypothermic Circulatory Arrest. (6th January 2021) - Bakhutashvili, Zviad; Janelidze, Lia; Beria, Kakhaber; Matikashvili, Simon; Limonjiani, Eduard
Abstract : A 60-year-old man presented with a thoracic aortic aneurysm without rupture accompanied by severe nonrheumatic aortic valve insufficiency and unstable angina. Surgery was performed and included several steps: (1) resection and reconstruction of ascending aorta and aortic arch using a tube graft, (2) replacement of aortic valve using a biological prosthesis, and (3) coronary artery bypass grafting was performed with two distal anastomoses. All of these procedures were performed with total cardiopulmonary bypass without deep hypothermic circulatory arrest under conditions of moderate hypothermia using dual concurrent cannulation of the subclavian and femoral arteries.